Adobe premiere pro CS6 digital classroom - Smith, Jerron; AGI Training Team; Adobe Systems (Indianapolis, Indiana John Wiley, 2012)
Includes 15 self-paced lessons that let you discover essential skills and explore the new creative possibilities allowed for in Adobe Premiere Pro CS6. Each lesson consists of step-by-step instructions, lesson files, along with video tutorials that complement the topics covered in each lesson, provided on the accompanying DVD.
A complete training package.
Includes index.
Keywords: Adobe Premiere; Digital video -- Editing -- Data processing